Should sputum smear examination be carried out at the end of the intensive phase and end of treatment in sputum smear negative pulmonary TB patients? - Sumit Malhotra (Public Library of Science (PLoS), 2012)
Background The Indian guidelines on following up sputum smear-negative Pulmonary tuberculosis (PTB) patients differ from the current World Health Organization (WHO) guidelines in that the former recommends two follow up sputum examinations (once at the end of intensive phase and the other at the end of treatment) while the latter recommends only one follow up sputum smear microscopy examination, which is done at the end of the intensive phase. This study was conducted to examine if there was any added value in performing an additional sputum smear examination at the end of treatment within the context of a national TB program. Methods This study was a descriptive record based review conducted in nine tuberculosis (TB) units in Delhi, India. All consecutive new sputum smear-negative PTB patients registered in these nine TB units from 1(st) January 2009 to 31(st) December 2009 were included in the study. Results Of 2567 new sputum smear-negative TB patients, 1973 (90%) had sputum specimens examined at the end of the intensive phase, of whom 36 (2%) were smear-positive: the majority (n = 28) successfully completed treatment with either the same or a re-treatment regimen. At treatment completion, 1766 (85%) patients had sputum specimens examined, of whom 16 (0.9%) were smear-positive: all these were changed to a re-treatment regimen. Amongst the sputum-positive patients identified as a result of follow up (n = 52), four were diagnosed with multi-drug resistant TB (MDR-TB), three of whom were detected after smear examination at the end of treatment. Conclusions Given the high burden of TB in India, a 0.9% additional yield of smear-positive sputum smears at the end of treatment translates to 3,297 cases of smear-positive PTB. End-of-treatment smear is a low-yield strategy for detection of smear-positive TB cases, although further studies are needed to determine its population-level impact and cost, particularly in relation to other TB control interventions.